Exploring the Impact of Emerging Forms of Nicotine on Adolescent Mental Health - Arman, Ayse Rodopman (Addicta: The Turkish Journal on Addictions, 2023)
Nicotine, the highly addictive psychoactive component of tobacco, acts on nicotinic acetylcholine receptors, influencing reward, motivation, attention, learning, and memory. Genetic background, sex, age, and environmental factors contribute to individual differences in nicotine addiction. The use of tobacco products is typically initiated and established during adolescence, when the developing brain is most susceptible to nicotine addiction. A significant reorganization of brain regions essential for advanced cognitive and executive functions and motivated behavior characterize the adolescent period. The neuro-inflammatory effects of nicotine have the most damaging impact on the adolescent brain. Many experts suggest that using e-cigarettes may lead to a higher likelihood of tobacco smoking addiction, acting as a “gateway” to stronger substances. The variety of e-cigarette flavors can affect pleasure perception and directly impact the brain reward system of the younger population. Therefore, it is crucial to avoid smoking or using any nicotine-containing products during this time to ensure optimal brain health and development. This article will explore the latest research on nicotine exposure and its impact on adolescent brain development. The review article discusses demographic features, neurophysiological effects of nicotine, contextual and individual differences in addiction, vulnerability to mental disorders, and e-cigarette use in adolescence.